Long interspersed nuclear element-1 retroelements are expressed in patients with systemic autoimmune disease and induce type I interferon - Mavragani, Clio P. (Arthritis Rheumatol, 2016)
OBJECTIVE: Increased type I interferon (IFN-I) and a broad signature of IFN-I-induced gene transcripts are observed in patients with SLE and other systemic autoimmune diseases. To identify disease-relevant triggers of the IFN-I pathway we investigated whether endogenous virus-like genomic repeat elements, normally silent, might be expressed in patients with systemic autoimmune disease, activate an innate immune response and induce IFN-I. METHODS: Expression of IFN-I and long interspersed nuclear element-1 (LINE-1; L1) was studied in kidney tissue from lupus patients and minor salivary gland (MSG) tissue from patients with primary Sjogren’s syndrome (SS) by PCR, western blot and immunohistochemistry. Induction of IFN-I by L1 was investigated by transfection of plasmacytoid dendritic cells (pDCs) or monocytes with an L1-encoding plasmid or L1 RNA. Involvement of innate immune pathways and altered L1 methylation were assessed. RESULTS: L1 mRNA transcripts were increased in lupus nephritis kidneys and in MSG from SS patients and correlated with IFN-I expression and L1 DNA demethylation. L1 open reading frame 1/p40 protein and IFNβ were expressed in MSG ductal epithelial cells and in lupus kidneys, and IFNα was detected in infiltrating pDCs. Transfection of pDCs or monocytes with L1-encoding DNA or RNA induced IFN-I. Inhibition of TLR7/8 reduced L1 induction of IFNα in pDCs and an inhibitor of IKKε/TBK1 abrogated induction of IFN-I by L1 RNA in monocytes. CONCLUSION: L1 genomic repeat elements represent endogenous nucleic acid triggers of the IFN-I pathway in SLE and SS and may contribute to initiation or amplification of autoimmune disease.